2015
DOI: 10.1155/2015/392326
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Antifungal Activity of Gemini Imidazolium Compounds

Abstract: The progress of antimicrobial therapy contributes to the development of strains of fungi resistant to antimicrobial drugs. Since cationic surfactants have been described as good antifungals, we present a SAR study of a novel homologous series of 140 bis-quaternary imidazolium chlorides and analyze them with respect to their biological activity against Candida albicans as one of the major opportunistic pathogens causing a wide spectrum of diseases in human beings. We characterize a set of features of these comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In recent years, our team has studied the synthesis, biological and surface activity, and structure–activity relationships (SAR) of quaternary ammonium salts. In the scope of our interest are mainly mono- and bis-imidazolium salts [ 15 , 16 , 17 ]. We found that the following structures of bis-imidazolium chlorides have the optimal antimicrobial activity: 3,3’- (α, ω-dioxaalkane) bis (1-alkylimidazolium chloride), which has at least six carbon atoms in its linker, and has a R substituent of C7 to C11; α, ω-bis [(alkane) imidazol-1-yl-3-alkoxymethyl] chloride, which has at least five carbon atoms in the linker, and has a C7 to C13; and 3,3’- (α, ω-dioxaalkane) bis (1-alkylimidazolium) chloride or α, ω-bis [(alkane) imidazol-1-yl-3- alkoxymethyl chloride], which has at least seven carbon atoms and has a substituent R of C7 to C11.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our team has studied the synthesis, biological and surface activity, and structure–activity relationships (SAR) of quaternary ammonium salts. In the scope of our interest are mainly mono- and bis-imidazolium salts [ 15 , 16 , 17 ]. We found that the following structures of bis-imidazolium chlorides have the optimal antimicrobial activity: 3,3’- (α, ω-dioxaalkane) bis (1-alkylimidazolium chloride), which has at least six carbon atoms in its linker, and has a R substituent of C7 to C11; α, ω-bis [(alkane) imidazol-1-yl-3-alkoxymethyl] chloride, which has at least five carbon atoms in the linker, and has a C7 to C13; and 3,3’- (α, ω-dioxaalkane) bis (1-alkylimidazolium) chloride or α, ω-bis [(alkane) imidazol-1-yl-3- alkoxymethyl chloride], which has at least seven carbon atoms and has a substituent R of C7 to C11.…”
Section: Introductionmentioning
confidence: 99%
“…The analyzed information system was divided randomly into a training and a test set, according to stratified cross-validation scheme, in a ratio of 4 to 1, i.e., 5-fold cross-validation [ 29 ]. Decision rules induced from the training set were checked on the validation set.…”
Section: Methodsmentioning
confidence: 99%
“…They showed that diallyl disulphide-loaded niosomes complex decreased the fungal cells and increased the life of cell tissue in contrast to the free formulation. Pałkowski et al [100] investigated the structure-activity relationship of gemini imidazolium compounds using the chemical structure and surface-active properties and antifungal activity against C. albicans ATCC 90028 strain. They remarked that antifungal activity depends not only on the surface-active properties of the compound but also on the substituent type and the position at the chloride moiety of substituents.…”
Section: Novel Active Compounds For Candidiasis Treatmentmentioning
confidence: 99%